TRACEABILITY SYSTEMS FOR INDONESIAN COCOA UNDER THE EUROPEAN UNION DEFORESTATION REGULATION (EUDR): CHALLENGES AND POLICY OPTIONS - Muhammad Obie (Kirana Publisher, 2026)
The European Union Deforestation Regulation (EUDR) introduces new requirements for agricultural commodity supply chains by mandating traceability, legality, and deforestation-free production. As one of the world's major cocoa-producing countries, Indonesia faces increasing pressure to strengthen traceability systems to maintain access to international markets, particularly the European Union. This study aims to examine the current state of traceability systems in Indonesia’s cocoa sector, identify key implementation challenges, and formulate policy options to support EUDR compliance. The study employs a desk study approach based on the review of regulatory documents, official reports, policy papers, and recent academic literature related to cocoa governance, traceability, and sustainability standards. The findings indicate that Indonesia has initiated several traceability-related programs, yet significant challenges remain, including fragmented data systems, incomplete farmer registration, limited geolocation information, weak institutional coordination, and unequal capacities among smallholder farmers. Strengthening digital traceability infrastructure, improving stakeholder coordination, enhancing farmer participation, and integrating traceability into national cocoa governance are essential for successful compliance. The study concludes that traceability should be viewed not only as a regulatory requirement but also as a strategic instrument for improving transparency, sustainability, and competitiveness in Indonesia’s cocoa sector.